(untitled) (Numerus academy review, 2026)
The analogy is the more Arabic methods present in Arabic poetry. His interest and sanctification made the poets competing to come up with the finest metaphors, using most of its types – analogy- which includes the digressive (circular) analogy. The research here reveals what is the digressive analogy, because many people are unaware of it. It also stands on its artistic side, through the poetic evidence obtained from the the old Arabic poetry.